Association of IL-10 Gene Polymorphism With IL-10 Secretion by CD4 and T Regulatory Cells in Human Leprosy - Tarique, Mohammad; Naz, Huma; Saini, Chaman; Suhail, Mohd; Shankar, Hari; Khanna, Neena; Sharma, Alpana (Frontiers in Immunology, 2020)
Leprosy is a chronic bacterial disease caused by Mycobacterium leprae. Cytokines are known to play vital role as a peacekeeper during inflammatory and other immunocompromised conditions such as leprosy. This study has tried to bridge the gap of information on cytokine gene polymorphisms and its potential role in the pathogenesis of leprosy. Interleukin-10 (IL-10) is an immunosuppressive cytokine, found to be elevated in leprosy that accounted for the suppression of host’s immune system by regulating the functions of other immune cells. T helper cells and T regulatory (Tregs) cells are the major source of IL-10 in lepromatous leprosy patients. In this study, we have documented the role of IL-10 cytokine gene polymorphism with the disease progression. A total of 132 lepromatous leprosy patients and 120 healthy controls were analyzed for IL-10 cytokine gene polymorphisms using PCR-SSP assay and flow cytometry was used to analyze IL-10 secretion by CD4 and Tregs in various genotype of leprosy patients. The frequencies of IL-10 (-819) TT and IL-10 (-1082) GG genotypes were significantly higher in leprosy patients as compared to healthy controls. This observation advocates that these genotypes were associated with the susceptibility and development of the disease. In addition, flow cytometry analysis demonstrated an increased number of IL-10 producing CD4 and Treg cells in IL-10 (819) TT genotype compared to CT and CC genotypes. These observations were further supported by immunohistochemical studies. Therefore, we can conclude that IL-10 cytokine gene polymorphisms by affecting its production can determine the predilection and progression of leprosy in the study population.